EFEKTIFITAS MULTI METODE DALAM MENINGKATKAN KEMAMPUAN CARA MAKAN BAGI ANAK TUNAGRAHITA SEDANG KELAS III DI SDLBN 35 PAINAN - Nenden Agustin (Universitas Negeri Padang, 2014)
Abstrack: this research was motivated by the problems that researchers have found in mental retardation children in III grade painan. Children have difficulties in the ability to eat right with the existing measures, so that the apparent absence of the child’s independence in eating activities. According to that problem, the researchers want to prove that multiple methods can improve the way kids eat for mental retardation III grade in SDLB 35 painan. This type of research is experimental in from (SSR) using A-B-A design and data analysis chart. Subjects of the percentage of the child’s ability in activities way of eating.